PENGEMBANGAN ACHIEVEMENT MAHASISWA DALAM MENGHADAPI UJIAN KONPREHENSIF TAFSIR HADIS (Studi pada Jurusan SPM Fakultas Syariah dan Hukum UIN Ar-Raniry) - Rahmat Efendy Siregar (IAIN Padangsidimpuan, 2016)
Strategic role of UIN Ar-Raniry in growth and development of society in Aceh has been done by alumni who have spread in that regions. The Shari’ah and Law Faculty has become a reference in solving various problems which related to Islamic law. In facing that challenge, the students of The Shari’ah and Law Faculty especially SPM students was given knowledge related to Islamic laws. One of the subject related to Tafsir and Hadis, such as Ulumul Qur’an, Tafsir,Tafsir Ahkam, Ulumu Hadis, Hadis and Hadis Ahkam. But, it was found there were various factors which caused SPM students have low ability in comprehensive examination of Tafsir Hadis. Whereas, these are as standards to know the understanding of that subject. One of the reason was SPM students graduated from general school (non-Islamic school). To increase students’ ability in mastering that subject, in his research was explained some tips which can be done by students to achieve success in education at college